EBUS versus EUS‐B for diagnosing sarcoidosis: The International Sarcoidosis Assessment (ISA) randomized clinical trial - Crombag, Laurence M. M.; Mooij‐Kalverda, Kirsten; Szlubowski, Artur; Gnass, Maciej; Tournoy, Kurt G.; Sun, Jiayuan; Oki, Masahide; Ninaber, Maarten K.; Steinfort, Daniel P.; Jennings, Barton R.; Liberman, Moishe; Bilaceroglu, Semra; et al. (Respirology (Carlton, Vic.), 2022)
Background and objective Endosonography with intrathoracic nodal sampling is proposed as the single test with the highest granuloma detection rate in suspected sarcoidosis stage I/II. However, most studies have been performed in limited geographical regions. Studies suggest that oesophageal endosonographic nodal sampling has higher diagnostic yield than endobronchial endosonographic nodal sampling, but a head‐to‐head comparison of both routes has never been performed. Methods Global (14 hospitals, nine countries, four continents) randomized clinical trial was conducted in consecutive patients with suspected sarcoidosis stage I/II presenting between May 2015 and August 2017. Using an endobronchial ultrasound (EBUS) scope, patients were randomized to EBUS or endoscopic ultrasound (EUS)‐B‐guided nodal sampling, and to 22‐ or 25‐G ProCore needle aspiration (2 × 2 factorial design). Granuloma detection rate was the primary study endpoint. Final diagnosis was based on cytology/pathology outcomes and clinical/radiological follow‐up at 6 months. Results A total of 358 patients were randomized: 185 patients to EBUS‐transbronchial needle aspiration (EBUS‐TBNA) and 173 to EUS‐B‐fine‐needle aspiration (FNA). Final diagnosis was sarcoidosis in 306 patients (86%). Granuloma detection rate was 70% (130/185; 95% CI, 63–76) for EBUS‐TBNA and 68% (118/173; 95% CI, 61–75) for EUS‐B‐FNA (p = 0.67). Sensitivity for diagnosing sarcoidosis was 78% (129/165; 95% CI, 71–84) for EBUS‐TBNA and 82% (115/141; 95% CI, 74–87) for EUS‐B‐FNA (p = 0.46). There was no significant difference between the two needle types in granuloma detection rate or sensitivity. Conclusion Granuloma detection rate of mediastinal/hilar nodes by endosonography in patients with suspected sarcoidosis stage I/II is high and similar for EBUS and EUS‐B. These findings imply that both diagnostic tests can be safely and universally used in suspected sarcoidosis patients. This global RCT in patients with suspected sarcoidosis stage I/II with an indication for endosonographic nodal sampling showed a similarly high granuloma detection rate and sensitivity for diagnosing sarcoidosis with endobronchial ultrasound versus endoscopic ultrasound‐B. The findings imply that both diagnostic tests (endobronchial/oesophageal) can be used safely and universally in suspected sarcoidosis patients.